Knowledge and Perspectives on the Welfare of Italian Heavy Pigs on Farms - Marika Vitali; Eleonora Nannoni; Luca Sardi; Giovanna Martelli (Animals, 2021)
This review aims to give an overview of the most significant available information on welfare issues of Italian heavy pigs on farms. These animals, whose meat is used to produce typical products, are characterized by much higher body weights and age at slaughter (approximately 160–170 kg, and 9 months of age) than most pigs reared in Europe, resulting in peculiar behavioral and rearing-related needs. To highlight the main findings and the areas in which additional research is needed, the paper was organized by allocating the studies on the basis of the Welfare Quality four principles framework, i.e., good feeding, good housing, good health, and appropriate behavior. The results indicate the possibility of improvement with regard to the management of feeding, watering, and some environmental parameters (light, thermal comfort, enrichments) and a lack of knowledge on the actual space requirements (and a corresponding regulatory gap). Moreover, deficiencies concerning the prevalence of injuries and disease and the relationship between lesions observed post-mortem and rearing conditions needs to be addressed. Lastly, the absence of research concerning the evaluation of the emotional state of animals has been highlighted. It is hoped that these findings will, in the future, serve as a basis for the development of specific policies for these animals in order to increase the ethical value of the entire production chain, in accordance with consumers’ demand and expectation for high animal welfare standards.